The Wheels That Drove New York A History of the New York City Transit System - Roess, Roger P. (Springer Tracts on Transportation and Traffic, 2013)
The Wheels That Drove New York tells the fascinating story of how a public transportation system helped transform a small trading community on the southern tip of Manhattan island to a world financial capital that is home to more than 8,000,000 people.  From the earliest days of horse-drawn conveyances to the wonders of one of the world's largest and most efficient subways, the story links the developing history of the City itself to the growth and development of its public transit system.  Along the way, the key role played by the inventors, builders, financiers, and managers of the system are highlighted. The Wheels That Drove New York takes us through the present day, and discusses the many challenges that the transit system has had to face over the years.  It also traces the conversion of the system from fully private operations (through the elevated railways) to the fully public system that exists today, and the problems that this transformation has created along the way.